Sistema de gestão logística e patrimonial do SESC: um estudo de caso - Ribeiro, João Martins (2003)
This study had as objective to consider if the Property and Logistic Administration System (PLS) developed for the SESC National Managements, supply the necessities of their Regional Managements, showing positive and negative points. Involving the areas of suppliment logistic, internallogistic and permanent movable resources management, the study had also as objective to establish a methodology of evaluation, since we had not found a similar case applied in services providing organizations. The methodology treated the general aspects related to the most important activities of humans resources, the efficiency of the tasks and the quality and the security of the information, everything resulting from the utility of information technology. Specifically, the methodology treated the focal points of the areas which form the study: information, register, processing, accompaniment, receiving and planning. The method also inc1udes the evaluation of the necessity of deve10ping the logistic module of PLS distribution. The results of the study showed that the PLS supplies the necessities of the SESC Regional Management and that the necessity of developing the logistic module must be better analyzed and that the methodology seemed to be viable and must be a motive for new researches of services providing organizations, inc1usively in SESC, as the model creates impacts in the management of logistic and property activities.